AMBIGUITAS STATISTIKA DESKRIPTIF & STATISTIKA INFERENSIAL - Jim Hoy Yam (PELITA JURNAL PENELITIAN DAN KARYA ILMIAH, 2020)
There is ambiguity of descriptive statistics and inferential statistics, which are applied on a scientific research paper. First ambiguity: Is it appropriate to apply 2 types of statistic in a research? And the second ambiguity: whether inferential statistics can utilize non-probability sample data? Those 2 questions motivate me to write this paper.?? The aim are to find answers of the ambiguity; by based on research behavior phenomenon, which are referring to research theory and research theorem. At the eventually, the conclusion, descriptive statistics and inferential statistics are need to be joined in a study to shake of the research output in terms to describing data of population or sample, then followed by data testing and data analyzing to draw conclusions. While the next ambiguity concerning of using non probability sampling by inferential statistic; it have been done by some researchers, with the excuse of result achievement closer to actual condition.